Evaluation of Mathematics Learning in the Digital Era: Challenges and Opportunities - Sidabutar, Ropinus (Lembaga Riset Mutiara Akbar, 2024)
The advancement of digital technology has transformed various aspects of life, including education. In mathematics education, technology offers numerous opportunities to enhance the effectiveness of learning but also presents significant challenges. This paper aims to evaluate mathematics learning in the digital era, focusing on the challenges and opportunities involved. This study employs a literature review method with descriptive analysis of relevant studies. Digital technology has great potential to improve accessibility, personalization, and interactivity in mathematics learning. Through technology-based learning platforms, students can access materials that were previously difficult to reach, visualize abstract concepts, and engage in independent and collaborative learning. Additionally, adaptive algorithms and artificial intelligence provide personalized learning experiences that can improve student outcomes. However, several challenges also arise, including digital inequality, limited teacher competence, curriculum adaptation, and the risk of over-reliance on technology, which may hinder students' deep understanding of basic mathematical concepts. To optimize these opportunities, synergy among technology, educators, and educational policies is essential. Thus, this paper provides insights into strategic steps to enhance the quality of mathematics learning in the digital era while addressing the existing challenges.